Prediction of Oxygen Distribution in Silos and Chambers Filled with Various Agricultural Commodities - Efstathios Kaloudis; Paraskevi Agrafioti; Christos Athanassiou (Agronomy, 2023)
In the context of post-harvest pest management in agricultural products, the adoption of modified atmospheres presents an eco-friendly alternative to conventional pesticides. This study focuses on nitrogen gas as a potential agent for insect control in stored commodities, utilizing computational simulations (by employing the convection–diffusion equation) to investigate its penetration and distribution within two common storage configurations: chamber-contained pallets and silos. The results highlight the influence of boundary conditions, commodity porosity, and convection effects on nitrogen dispersion. In chamber scenarios, the first boundary condition considers that pallets are placed inside a chamber with uniform (99.5%) nitrogen concentration, whereas in the second one, the concentration gradually increases from 78% to 99.5%. The average duration required for O<semantics>2</semantics> concentration to reach 1% is approximately 10.7 h and 133.3 h for the two boundary conditions, respectively. Among the agricultural commodities, walnuts (kernels) exhibit the shortest duration, while prunes require the longest time. In silos, convection and diffusion interact to establish a consistent diffusion layer thickness. Most agricultural products exhibit similar behavior, with average times of 13.5 h, 25.4 h, and 37.0 h for three heights (10 m, 20 m, and at the silo’s top at 30 m), respectively.